The Physical and Chemical Characteristics of Potato Doughnuts Using Semi-Liquid Local Yeast Derived from Myrrh of Red Fermented Palm Sap - Regina Ilse Marcelina BanoEt (Journal of Sustainable Development Science, 2021)
Natural or local yeasts are microorganisms from natural ingredients obtained from fermentation without the need for artificial additives. The objectives of the present study were 1.) to evaluate the physical quality of potato doughnuts produced from the local yeast derived from residue of red fermented palm sap, 2) to obtain the best treatment from the use of local yeast in making doughnuts. In the fermentation process, yeast converts sugar and carbohydrates in the dough into carbon dioxide gas (CO2) and alcohol. Doughnuts are made from wheat flour, but the addition of potato paste can improve the texture so that it is softer and tender due to the interaction between gelatinized starch and gluten but can reduce its swelling power. The experiment was designed using a completely randomized design (CRD) with three treatments and five replications to produce 15 experimental units. The treatments were a) Control (commercial yeast); b) Wheat flour: potato paste: local yeast; 2:1:1; c) Wheat flour: potato paste: local yeast; 2:1:2 and d) Wheat flour: potato paste: local yeast; 2:1:3. The results showed that the best treatment formula was obtained in the treatment B (wheat flour: potato paste: local yeast; 2:1:1) with 20,6% moisture content, 2,09% protein content and 3,644 color value (very like), 3,800 taste value (very like) and texture/tenderness with a value of 1032,500.